2008
DOI: 10.1111/j.1365-2923.2008.03161.x
|View full text |Cite
|
Sign up to set email alerts
|

MOR: a simulation-based assessment centre for evaluating the personal and interpersonal qualities of medical school candidates

Abstract: MOR is a reliable tool for measuring non-cognitive attributes in medical school candidates. It has high content and face validity. Furthermore, its implementation conveys the importance of maintaining humanist characteristics in the medical profession to students and faculty staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 20 publications
2
70
0
4
Order By: Relevance
“…These can be grouped into ''paper and pencil'' assessments of personality traits (e.g., Adams et al 2012Adams et al , 2015Bore et al 2005a, b;Dowell et al 2011;Fukui et al 2014;James et al 2013;Lumsden et al 2005;Manuel et al 2005;Nedjat et al 2013), structured multiple interview approaches (Dore et al 2010;Eva et al, 2004aEva et al, , b, 2009Hofmeister et al 2008Hofmeister et al , 2009O'Brien et al 2011;Reiter et al 2007;Roberts et al 2008;Rosenfeld et al 2008), selection centres (Gafni et al 2012;ten Cate and Smal 2002;Ziv et al 2008;Gale et al 2010;Randall et al 2006a, b) and-the ''new kid on the block''-situational judgement tests (Christian et al 2010;Koczwara et al 2012;Lievens 2013;Lievens et al 2008;Patterson et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…These can be grouped into ''paper and pencil'' assessments of personality traits (e.g., Adams et al 2012Adams et al , 2015Bore et al 2005a, b;Dowell et al 2011;Fukui et al 2014;James et al 2013;Lumsden et al 2005;Manuel et al 2005;Nedjat et al 2013), structured multiple interview approaches (Dore et al 2010;Eva et al, 2004aEva et al, , b, 2009Hofmeister et al 2008Hofmeister et al , 2009O'Brien et al 2011;Reiter et al 2007;Roberts et al 2008;Rosenfeld et al 2008), selection centres (Gafni et al 2012;ten Cate and Smal 2002;Ziv et al 2008;Gale et al 2010;Randall et al 2006a, b) and-the ''new kid on the block''-situational judgement tests (Christian et al 2010;Koczwara et al 2012;Lievens 2013;Lievens et al 2008;Patterson et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally there is increasing evidence that a diverse group of decision-makers and problem-solvers results in better decision-making. 17,18 When there is only a slight surplus of applicants to seats in a class, it is imperative that admissions committees and officers have criteria other than grade point averages and PCAT scores to help assess the likelihood that a candidate who does not score as well as others in those objective measures of cognitive performance will make up for any deficiencies with outstanding non-cognitive performance. The reality is that not all our applicants will have top scores on the standardized tests and selecting among those who do not is a challenge for most admissions committees.…”
Section: Discussionmentioning
confidence: 99%
“…28 Many college admissions administrators and faculty express a desire to effectively measure the non-cognitive traits of a candidate because students with strong non-cognitive skills tend to be more engaged in the learning process, motivated to succeed, committed to lifelong learning, and appreciate the effort required to be successful. 17,21,26,27,29,30,31,32,33 Furthermore, as Hamilton and Freeman stated quite some time ago, "As the demand for higher education increases, questions are bound to be asked that have profound bearing on the usefulness of the methods of selection, on educational ideals and aims, and whether the results justify the money and effort invested". 34 Finally, a study conducted by Adebayo revealed, while traditional cognitive measures were a valid predictor of success for fully admitted students, conditionally admitted students tend to have better predictors of success with a combination of both cognitive and non-cognitive measures.…”
Section: Holistic Review and Access To Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…551 to deliver (Ziv et al 2008), However, research suggests that MMIs/SCs may provide 552 greater depth and breadth of information about candidates than structured interviews 553 (Randall et al 2006a, b), suggesting that their cost effectiveness may therefore be good 554 when balanced against the increased validity (and thus reduced extended training costs) 555 they may offer (Pau et al 2013;Rosenfeld et al 2008). 556…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%